Assessment of chemical, microbiological and sensory quality of Sous vide cooked Luciobarbus esocinus (Heckel, 1843) during chilled storage - Inanli, Ayse Gurel; Yaz, Yelda (Mattioli 1885, 2020)
The aim of this study was to investigate chemical, microbiological and sensory quality of sous-vide cooked Luciobarbus esocinus (Heckel, 1843) during chilled storage. Moisture, ash, fat, protein, salt, pH, total volatile basic nitrogen (TVB-N), thiobarbituric acid reactive substances (TBARs), counts of aerobic mesophile bacteria, aerobic psychrophile bacteria and yeast-mold were determined in the raw material. The sensorial, chemical and microbiological changes of products obtained under the cold storage were analyzed in 3 days interval with three replicates. TermsTVB-N value in group C was determined as 11.06 mg/100 g, in the S1 group as 10.40 mg/100 g, and in the S2 group as 11.99 40 mg / 100 g (p<0.05). At the beginning of storage, TBARs value was found to be 1.58 MDA/kg in traditionally processed fish, 1.42 MDA/kg in S1 samples, and 1.28 mg MDA/kg in S2 samples. As. The average count of aerobic mesophile bacteria of S1 group was 3.65 +/- 0.03 log CFU g(-1) on the 1st day. On the 15th day of the storage, however, it exceeded the limit value. For the S2 samples, this was 3,17 +/- 0,60 log CFU g(-1) on the 1st day while on the 18th day, it exceeded the limit value. Aerobic psychrophile bacteria count was 3.45 +/- 0.13 log CFU g(-1) in C group, 3.08 +/- 0.58 log CFU g(-1) in S1 group and 2.14 +/- 0.99 log CFU g- 1 in S2 group. Yeast mold count was 3.93 +/- 0.29 log CFU g(-1) in the C group, 4.09 +/- 0.08 log CFU g(-1) in the S1 group, and 2,81 +/- 0,47 log CFU g(-1) in the S2 group. It was observed that products prepared according to the sous-vide method are liked considerably. In conclusion; the results suggested that the C application would be a promising approach to limit microbial growth and provide food safety for sous-vided samples. It was determined that application of sous-vide technology had a positive affect upon shelf life of fish products.
Keywords: Luciobarbus esocinus; Sous-Vide; Cold Storage; Shelf Life